2004
DOI: 10.1093/jnci/djh301
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Antigen Presentation and Effectiveness of Combined Active/Passive Immunotherapy for Epithelial Tumors

Abstract: Antigen-specific CD8+ T cells can destroy epithelium expressing HPV16 E7 tumor antigen, but presentation of E7 antigen from skin is insufficient to reactivate memory CD8+ T cells induced by immunotherapy. Thus, effective cancer immunotherapy in humans may need to invoke sufficient effector as well as memory T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 36 publications
1
82
3
Order By: Relevance
“…Using a murine model of skin grafting, we were able to mimic the immunosuppressive, hyperplastic lesions of HPV infection, which are a determinant of progression to cervical cancer. HPV16-E7-expressing skin transplanted onto sygeneic, immunocompetent hosts attracts inflammatory cell infiltrates; however, these grafts are not rejected (16,17). The underlying mechanism of immune resistance to these grafts is undefined.…”
mentioning
confidence: 99%
“…Using a murine model of skin grafting, we were able to mimic the immunosuppressive, hyperplastic lesions of HPV infection, which are a determinant of progression to cervical cancer. HPV16-E7-expressing skin transplanted onto sygeneic, immunocompetent hosts attracts inflammatory cell infiltrates; however, these grafts are not rejected (16,17). The underlying mechanism of immune resistance to these grafts is undefined.…”
mentioning
confidence: 99%
“…Furthermore, immunisation with vaccines that are known to reject E7 producing transplantable tumours, also failed to reject E7 skin grafts (11,12). This result contrasts to similar skin-grafting experiments where other proteins are used as transgenes, e.g, ovalbumin protein (OVA) & human growth hormone: such grafts spontaneously reject within 20 days (13,14). These findings suggested that the fate of grafts is antigen dependant, and suggested the existence of a mechanism leading to E7 tolerance which could explain the failure of E7 therapeutic vaccination.…”
Section: Introductionmentioning
confidence: 93%
“…Grafts intact at day 200 post-surgery were retained as nonrejected. Skin graft rejection was assessed as described (14).…”
Section: Skinmentioning
confidence: 99%
“…The preparation of HPV16E7 protein has been previously described [28]. The H-2D b -restricted CTL epitope, HPV16 E7 49-57 [29], with the amino acid sequence RAHYNIVTF (E7 peptide), the H-2K b -restricted epitope, OVA 257-264 [30], with the amino acid sequence SIINFEKL, the H-2K b -restricted epitope, SVN 324-332 [31], with the amino acid sequence FAPGNYPAL, a polyepitope peptide containing all three CTL peptides without spacers, an HPV16E7 antibody epitope, with the amino acid sequence EIDGPAGQAEPDRAHYNIVTF, and an HPV16E7 CD4 epitope, with amino acid sequence QAEPDRAHYNIVTFCCKCD, were all purchased from Auspep Pty (Melbourne, Australia) with 470% purity.…”
Section: Reagentsmentioning
confidence: 99%
“…Serum antibodies including isotype-specific antibodies against HPV16E7 were measured by ELISA [35] and IFN-g levels in culture supernatants were assessed by capture ELISA [28] as previously described. Serum antibody titers were calculated as the highest dilution of post-immunization serum producing an absorbance value greater than three standard deviations above the absorbance value for pre-immunization serum from that group of mice.…”
Section: Generation Of E7-specific Tcr-b Transgenic Micementioning
confidence: 99%